Fifth Generation (5G) New Radio (NR) Channel Codes Contenders Based on Field- Programmable Gate Arrays (FPGA): A Review Paper (Journal of University of Babylon for Engineering Sciences, 2019)
The increased demands for quality, like high throughput, low-latency, wide coverage, energy consumption, cost and reliable connections in mobile services, multimedia and data transmission impose the use of advance technical requirements for the next fifth-generation (5G) new radio (NR). One of the most crucial parts in the physical layer of the new generation is the error correction coding technique. Three schemes, namely; Turbo, low density parity check (LDPC), and polar codes are potentially ‎considered as the candidate codes for both data and control channels. The competition is evaluated in terms of error correction capability, computational complexity, and flexibility. The parallelism, flexibility and high processing speed of Field-Programmable Gate Array (FPGA) make it preferable in prototyping and implementation of different codes. This paper presents a survey on the current literatures that deals with FPGA-based decoder design associated with the previously mentioned channel codes.